Effectiveness of a group intervention based on cognitive–behavioral approach on the levels of ambiguity tolerance, distress tolerance, and academic achievement motivation in students - Negar Sharafi Nashtban; Reza Aghajani; Somaieh Salehi (Journal of Education and Health Promotion)
BACKGROUND: Students who are about to take their final-year college entrance examinations experience considerable worries and psychological stress. Enhancing ambiguity tolerance, distress tolerance, and academic achievement motivation during this period can greatly contribute to their psychological well-being and academic success. The aim of this research was to determine the effectiveness of a group intervention based on a cognitive–behavioral approach on the levels of ambiguity tolerance, distress tolerance, and academic achievement motivation among students in this educational phase. MATERIALS AND METHODS: This study is a quasi-experimental research design with a pre-test, post-test design, and a 1-month follow-up with a control group. The population includes all students in District 16 of Tehran. Using convenience sampling, 20 male students from the high in District 16 were selected as the experimental group, and 20 of them were selected as the control group (using G*Power). The research instruments included the Second-Type Ambiguity Tolerance Questionnaire, Distress Tolerance Questionnaire, and Academic Achievement Motivation Questionnaire. Cognitive–behavioral therapy (CBT) sessions were conducted in a group format, following an 8-weekly session plan, with each session lasting 2 hours for the experimental group. Data were analyzed using repeated-measures analysis of variance (ANOVA). RESULTS: The results of the repeated-measures ANOVA showed that CBT had a significant effect on increasing ambiguity tolerance, distress tolerance, and academic achievement motivation (P < 0.05), and this effect remained stable during the follow-up stage. CONCLUSION: The results indicated that a group intervention based on the cognitive–behavioral approach increased ambiguity tolerance, distress tolerance, and academic achievement motivation in male students in their final year of high school (on the verge of college entrance examination). Therefore, these interventions are recommended for college-bound students to enhance their psychological well-being and academic success.